Public and scientific Novgorod Forum «Russian traditions of public administration»: analytical report - Y. V. Gimazova (Управление)
In article the report on holding the public and scientific forum «Russian Traditions of Public Administration» which has taken place on September 14, 2017 in Veliky Novgorod is suggested. Results of a public and scientific discourse on problems of national statehood genesis, in the context of relevant trends, calls and the prospects of geopolitical development of the Russian Federation in XXIV are comprehended. Positions of the famous Russian historians and political scientists on a ratio communal and bureaucratic are presented, within development of national statehood, from Old Russian till the imperial period. Problems of interaction of the power and the public are revealed: backwardness of an institutionalizing of political participation, low competence of the Russian bureaucracy of questions of intersectoral interaction, not accounting of national traditions of grass-roots democracy in questions of the choice of means and methods of development and realization of the Russian state policy, insufficient efficiency of public advisory. The perspective directions of further researches within the forum are revealed. Among them: ability to integrate values of the Novgorod veche democracy and «governmental» ideas of the Moscow and Imperial Russia for strengthening of bases and institutes of legal democratic statehood in modern Russia and the Novgorod region; realization by the Forum participants the joint research and educational projects aimed at the development of civil society institutes, identification of «bottlenecks» in the system of interaction between power and the public of the Novgorod region; development intellectual regions dialogue among the Northwest of Russia, the Baltic States and states of Northern Europe for the purpose of cultural historical links expansion, initiation and implementation of joint projects concerning improvement of life level, management of the territory development, strengthening of the international expert and analytical potential.